A summary history of the application of statistical catch-at-age analysis (SCAA) to Antarctic minke whales - Punt, Andre E. (J. Cetacean Res. Manage., 2023)
Various forms of SCAA methods have been applied to data for Antarctic minke whales since this method was first presented to the Scientific Committee of the International Whaling Commission by Punt and Polacheck (2005). A brief overview is provided of the historical use of methods which use catch-at-age data to draw inferences regarding trends in abundance for Antarctic minke whales. The original version of the SCAA and how this method has been modified over time to more adequately mimic the available data on length, conditional age-at-length and indices of abundance from IDCR/SOWER and JARPA/JARPAII is described. The paper also lists the specifications for the reference case analyses in each paper presented to the Scientific Committee. The focus is on methodology, with only limited comment on the results from each subsequent analysis.